Teachers’ First Meeting with Groups of Parents of Elementary Students at the Beginning of the School Year: Parents’ Expectations and Responses to these Expectations - Bergeron, Isabelle; Deslandes, Rollande (International Journal about Parents in Education, 2023)
This study examines the expectations of parents of elementary students with respect to the information evenings at the beginning of school year. The expectations are discussed in terms of welcoming, exchange of information and perceptions of the development of trust with their child’s teacher. Data collection was conducted with eight parents of fifth grade in the course of two interviews conducted with each participant, one before the group meeting, and a second one, a few days after. The results indicate that parents expect a warm and individualized reception, and information on strategies to support learning and work at home. Parents reported that there was no group discussion or exchange at the meeting which also did not serve to establish norms of collaboration based on educational goals or to identify actions aiming to develop the sharing of responsibilities. Parents, however, said that their child’s teacher inspires trust. Avenues for future research are discussed.